2019
DOI: 10.14639/0392-100x-2415
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Bell’s palsy: outcomes and correlation with clinical comorbidities

Abstract: SUMMARYRecurrent Bell’s palsy (RBP) has been reported to range from 2.6 to 15.2% of primary Bell’s palsy (BP) and has been associated with systemic comorbidities such as diabetes and hypertension. A retrospective analysis of patients affected by BP and RBP were performed to define the signs and symptoms associated with recurrence and the outcomes. Clinical and subjective characteristics of 341 patients affected by facial palsy were analysed. Facial function was assessed via House-Brackmann and Sunnybrook gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
4
9
1
Order By: Relevance
“…27,29,30 The results of the present study correspond with those of earlier studies that reported no association between comorbidities and recurrent Bell's palsy. 26,29 No high-quality trials have been conducted to explore the effectiveness of physiotherapy. 19,20,31 A large body of research has suggested that physiotherapy is not harmful and has small benefits in patients with severe Bell's palsy, such as those who have synkinesis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…27,29,30 The results of the present study correspond with those of earlier studies that reported no association between comorbidities and recurrent Bell's palsy. 26,29 No high-quality trials have been conducted to explore the effectiveness of physiotherapy. 19,20,31 A large body of research has suggested that physiotherapy is not harmful and has small benefits in patients with severe Bell's palsy, such as those who have synkinesis.…”
Section: Discussionsupporting
confidence: 91%
“…There has been considerable disagreement regarding the role of underlying comorbidities such as diabetes mellitus and hypertension in the recurrence of Bell's palsy. 27,29,30 The results of the present study correspond with those of earlier studies that reported no association between comorbidities and recurrent Bell's palsy. 26,29 No high-quality trials have been conducted to explore the effectiveness of physiotherapy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Recurrent Facial palsy have just a few know comorbidities risk factors, such as diabetes and hypertension [4] . On the other hand, there are a few known factors which can explain higher risk to get sick with Guillain-Barre syndrome, such as immune-mediated and rheumatological disease, cancer, transfusion, surgical procedures, and preeclampsia [3] .…”
Section: Discussionmentioning
confidence: 99%